Loop Antennas - Amit Mehta (Handbook of Antenna Technologies, 2016)
This chapter on loop antennas covers implementation aspects of both electrically small and electrically large loops which have a wide range of applications. On one side, they are still a part of the old broadcasting systems such as analog radios, and, on the other side, they are increasingly gaining attention for the contemporary high-definition video transmission and reception. The chapter begins with electrically small loops and coil antennas and covers its different aspects of radiation and losses, tuning, quality factor, and matching. Subsequently, resonant full-wave loops and their polarization are presented. A technique is shown on how loops can be placed in closed vicinity of a communicating device conducting surface without losing efficiency. In the final part, single-element beam steering loop antennas and their arrays for enabling devices to achieve high throughput and high-gain wide scanning range are discussed.